Artificial saliva effect on toxic substances release from acrylic resins - Kostić, Milena M; Krunić, Nebojša; Najman, Stevo; Nikolić, Ljubiša; Nikolić, Vesna; Rajković, Jelena; Petrović, Milica; Igić, Marko; Ignjatović, Aleksandra (Vojnosanitetski pregled, 2015)
Background/Aim. Acrylic-based resins are intensively used in dentistry practice as restorative or denture-base materials. The purpose of this study was to analyze the surface structure of denture base resins and the amount of released potentially toxic substances (PTS) immediately upon polymerization and incubation in different types of artificial saliva. Methods. Storage of acrylic samples in two models of artificial saliva were performed in a water bath at the temperature of 37 ± 1°C. Analysis of the surface structure of samples was carried out using scanning electronic microscopy analysis immediately after polymerization and after the 30-day incubation. The amounts of PTS per day, week and month extracts were measured using high-pressure liquid chromatography. Results. Surface design and amount of PTS in acrylic materials were different and depended on the types and duration of polymerization. The surfaces of tested acrylates became flatter after immersing in solutions of artificial saliva. The degree of acrylic materials release was not dependent on the applied model of artificial saliva. Conclusion. In order to improve biological features of acrylic resin materials, it was recommended that dentures lined with soft or hard cold-polymerized acrylates should be kept at least 1 to 7 days in water before being given to a patient. So, as to reach high degree of biocompatibility preparation of prosthetic restorations from heat-polymerized acrylate was unnecessary.